2013
DOI: 10.1161/circresaha.111.300193
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inhibition of Na + -Ca 2+ Exchanger Current Disables Fight or Flight Sinoatrial Node Activity Without Affecting Resting Heart Rate

Abstract: Rationale The sodium-calcium exchanger 1 (NCX1) is predominantly expressed in the heart and is implicated in controlling automaticity in isolated sinoatrial nodal (SAN) pacemaker cells, but the potential role of NCX1 in determining heart rate in vivo is unknown. Objective Determine the role of Ncx1 in heart rate. Methods and Results We employed global myocardial and SAN-targeted conditional Ncx1 knockout (Ncx1−/−) mice to measure the effect of the NCX current (INCX) in pacemaking activity in vivo, ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…Both of these models exhibit a much less severe phenotype in SAN cell function than our mice (2), which may be due to incomplete ablation of NCX. Nevertheless, there are certain similarities: Gao et al (6) showed an impaired response to ISO and Bay K, as we did; Herrmann et al (7) reported bursts alternating with pauses in ECG traces, comparable with our NCX KO SAN pattern.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Both of these models exhibit a much less severe phenotype in SAN cell function than our mice (2), which may be due to incomplete ablation of NCX. Nevertheless, there are certain similarities: Gao et al (6) showed an impaired response to ISO and Bay K, as we did; Herrmann et al (7) reported bursts alternating with pauses in ECG traces, comparable with our NCX KO SAN pattern.…”
Section: Discussionsupporting
confidence: 88%
“…BayK caused an increase in Ca transient frequency in WT SAN, consistent with prior studies (6,19). However, in KO, we obtained the opposite response (Fig.…”
Section: Intracellular Ca During Spontaneous Bursts and Electrical Stsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, 1 μmol/L glibenclamide and 100 μmol/L CdCl 2 were added to block ATP‐sensitive K + channels and voltage‐gated Ca 2+ channels. Pacemaker current (funny current [ I f ]) was recorded, as described 23. All current recording experiments were conducted at room temperature (21–23°C).…”
Section: Methodsmentioning
confidence: 99%